Exploring the Interaction Between Nursing Decision Making and Patient Outcomes in 2 European Cancer Centers: A Qualitative Study. Issue 5 (September 2018) - Valcarenghi, Dario; Bagnasco, Annamaria; Aleo, Giuseppe; Catania, Gianluca; Zanini, Milko; Cavaliere, Bruno; Carnevale, Franco; Sasso, Loredana
Abstract : Background: In some clinical settings, nurses have difficulty describing the outcomes of their caring activities. Understanding the reasons for this could help nurse leaders to improve the effectiveness and visibility of nursing practice and safeguard nurses' working conditions. Objective: The aims of this study were to understand how nurses working in 2 different adult cancer centers make healthcare decisions and assess the respective outcomes on their patients. Methods: Through a constructivist grounded theory approach, we involved 15 clinical cancer nurses with different experiences and educational backgrounds and 6 nurse managers, working in 2 comprehensive cancer centers, 1 in Italy and 1 in Switzerland. Data were collected in 2 phases using 20 semistructured interviews and 9 field observations. Results: Six macrocategories emerged: interacting with situational factors, deciding relevant interventions, using multiple decision-making approaches, evaluating interventions and reporting them, pursuing healthcare outcomes, and clarifying professional identity and roles. Nurses' decision-making processes varied and were influenced by various factors, which mutually influenced one another. This process was interpreted using an explicative theory called "dynamic decision-making adaptation." Conclusions: The present study showed how the aims, contents, and degree of autonomy in the nurses' decision-making process are strongly influenced by the dialectic interaction between professional and contextual factors, such as competency and professional identity. Implications for Practice: Cancer nurses could influence their clinical practice by developing nursing competencies that effectively resolve patients' problems. This is a key factor that nurses govern autonomously and therefore a responsibility that involves the entire nursing educational, organizational, and scientific leadership.